Policies for the management of compulsory public education in Ibero America: Introduction - Ângelo Ricardo de Souza; Sebastián Donoso Diaz; Joaquín Gairin Sallán (Arizona State University, 2020)
This paper presents the dossier Policies for the Management of Mandatory Public Education in Ibero America, which addresses elements of mandatory public-school management in the macro-region such as educational reforms, policies of teachers and principals training, universalization and inclusion policies, experiences and innovative models and the public-private relationship in education. The article that presents the dossier shows that the readings sampled in this EPAA special issue deal with themes, theories and experiences that are consistent with the idea that education is a universal right of the human person, mandatory and free to all during some period of life, under State responsibility, secular and with guarantee of quality for all.